2010
DOI: 10.2337/dc10-1288
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction in the Incidence of Type 2 Diabetes With the Mediterranean Diet

Abstract: OBJECTIVETo test the effects of two Mediterranean diet (MedDiet) interventions versus a low-fat diet on incidence of diabetes.RESEARCH DESIGN AND METHODSThis was a three-arm randomized trial in 418 nondiabetic subjects aged 55–80 years recruited in one center (PREDIMED-Reus, northeastern Spain) of the Prevención con Dieta Mediterránea [PREDIMED] study, a large nutrition intervention trial for primary cardiovascular prevention in individuals at high cardiovascular risk. Participants were randomly assigned to ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
387
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(410 citation statements)
references
References 25 publications
16
387
0
7
Order By: Relevance
“…The effects of nuts on insulin sensitivity are influenced strongly by changes in body weight, which may have accounted for the changes observed in one of these studies where participants reduced body weight with nut consumption. Longer intervention trials with Mediterranean diets supplemented daily with 20-50 g of walnuts or 30 g of mixed nuts (a mixture of walnuts, almonds and hazelnuts was used in the PREvencion con DIeta MEDiterranea (PREDIMED) trial as reported by Casas-Agustench et al (21) ) resulted in a reduction in fasting glucose, insulin and improvement in insulin sensitivity (homeostatic model assessment of insulin resistance; HOMA) (47) and the incidence of type 2 diabetes by 52 % over 4 years (30) . Benefits shown in studies with nuts included as part of the intervention diet (NORDIET (46) or Mediterranean diet (47) ) may have been partly due to other components of these diets (62) .…”
Section: Effects Of Nuts On Glucoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of nuts on insulin sensitivity are influenced strongly by changes in body weight, which may have accounted for the changes observed in one of these studies where participants reduced body weight with nut consumption. Longer intervention trials with Mediterranean diets supplemented daily with 20-50 g of walnuts or 30 g of mixed nuts (a mixture of walnuts, almonds and hazelnuts was used in the PREvencion con DIeta MEDiterranea (PREDIMED) trial as reported by Casas-Agustench et al (21) ) resulted in a reduction in fasting glucose, insulin and improvement in insulin sensitivity (homeostatic model assessment of insulin resistance; HOMA) (47) and the incidence of type 2 diabetes by 52 % over 4 years (30) . Benefits shown in studies with nuts included as part of the intervention diet (NORDIET (46) or Mediterranean diet (47) ) may have been partly due to other components of these diets (62) .…”
Section: Effects Of Nuts On Glucoregulationmentioning
confidence: 99%
“…Other bioactive nutrients in nuts may benefit glucoregulation (27) , endothelial function, blood pressure control (28) and inflammation (21) . Studies have demonstrated that higher nut consumers are at a significantly lower risk of non-cardiovascular inflammatory disease mortality (29) and risk of developing type 2 diabetes (30) than low nut consumers. These benefits may be attributed to their nutrient profile; plant-derived n-3 fatty acids (a-linolenic acid; ALA) found in walnuts have been shown in clinical and epidemiological studies to improve inflammation, arterial compliance, insulin resistance, endothelial function and blood pressure (31 -34) .…”
Section: Introductionmentioning
confidence: 99%
“…11 The results of this national, crosssectional study show that obese persons and persons with a carbohydrate metabolism disorder generally consumed less olive oil and that persons who consumed olive oil tended to have a lower prevalence of obesity and type 2 diabetes mellitus, supporting the hypothesis of a lower risk for obesity and type 2 diabetes mellitus in persons who consume olive oil, as found in several prospective studies 32,33 and in a recent clinical trial in persons at high risk for cardiovascular disease. 34 Of particular note was the association found between olive oil consumption and the population pattern of insulin resistance. Insulin resistance is generally agreed to increase with the consumption of saturated fatty acids 35 and decrease with the consumption of n-3 fatty acids, 36 with the effect of n-6 fatty acids being controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean Diet (MedDiet) is an example of a dietary pattern that provides evidence for an association between diet quality and healthy ageing [50][51][52][53]. There is evidence suggesting that greater adherence to a MedDiet is associated with substantial reductions in the risk of several major age-related diseases including cardiovascular disease (CVD) [54], overall cancer risk [55], type 2 diabetes mellitus (T2DM) [56][57][58] and cognitive decline [59,60].…”
Section: Introductionmentioning
confidence: 99%